2021
DOI: 10.1101/2021.08.20.21262334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of 42 Genome-Wide Significant Loci Associated with Dyslexia

Abstract: Reading and writing are crucial for many aspects of modern life but up to 1 in 10 children are affected by dyslexia [1, 2], which can persist into adulthood. Family studies of dyslexia suggest heritability up to 70% [3, 4], yet no convincing genetic markers have been found due to limited study power [5]. Here, we present a genome-wide association study representing a 20-fold increase in sample size from prior work, with 51,800 adults self-reporting a dyslexia diagnosis and 1,087,070 controls. We identified 42 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
101
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(128 citation statements)
references
References 53 publications
(62 reference statements)
8
101
0
Order By: Relevance
“…Genetic variation explains a substantial component of reading abilities, with twin-based heritability (twin-h 2 ) estimates of 0.66 (Andreola et al, 2021) and population-based heritability (SNP-h 2 ) estimates of 0.50 (Verhoef et al, 2020). The largest genome-wide association study (GWAS) of language and reading-related traits to date (N~34,000) has confirmed the robust heritability estimates for these traits, identifying a single genome-wide significant locus for word reading in chromosome 1 (Eising et al, 2021). This study has also highlighted a shared genetic component of reading-related measures with other cognitive components and the cortical surface area (CSA) of the banks of the left superior temporal sulcus (STS; Eising et al, 2021).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Genetic variation explains a substantial component of reading abilities, with twin-based heritability (twin-h 2 ) estimates of 0.66 (Andreola et al, 2021) and population-based heritability (SNP-h 2 ) estimates of 0.50 (Verhoef et al, 2020). The largest genome-wide association study (GWAS) of language and reading-related traits to date (N~34,000) has confirmed the robust heritability estimates for these traits, identifying a single genome-wide significant locus for word reading in chromosome 1 (Eising et al, 2021). This study has also highlighted a shared genetic component of reading-related measures with other cognitive components and the cortical surface area (CSA) of the banks of the left superior temporal sulcus (STS; Eising et al, 2021).…”
Section: Introductionmentioning
confidence: 89%
“…Dyslexia also has a complex genetic and environmental aetiology, with twin-h 2 estimates of 0.40-0.60 (Fisher & DeFries, 2002) and SNP-h 2 estimates of 0.15-0.19 (Doust et al, 2021; Gialluisi et al, 2020). Another recent GWAS study with an unprecedented sample size identified 42 loci associated with dyslexia at the genome-wide significant level, consistent with high polygenicity of the trait (Doust et al, 2021). Recently, the brain imaging genetics field has also been revolutionized by meta-analytic efforts (Grasby et al, 2020) and large-scale datasets such as the UK Biobank (UKB; Elliott et al, 2018; Smith et al, 2021), providing new insights into the role genetics play shaping brain structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possibility is that the ambidexterity measure (reported as "being able to write with both hands") may be a consequence of injuries that force the use of the nonpreferred hand. However, to further complicate the situation a very recent genetic study for dyslexia-a neurodevelopmental phenotype-found a significant genetic correlation with the UK Biobank ambidexterity measure (but not with left-handedness) in over a million individuals derived from the 23andMe database [23]. The results of these studies show that even extremely large samples are not sufficient to disentangle patterns of associations between various binary traits and emphasise the importance of the quality of the phenotypes used for genetic studies.…”
Section: How To Measure Handednessmentioning
confidence: 99%
“…Crucially, GWAS of complex (non-Mendelian) traits such as speech and reading would require very large sample sizes in order to reproducibly capture genetic associations of interest ( Deriziotis and Fisher, 2017 ). Recent advances in the genetic architecture of dyslexia in a sample of over one million participants ( Doust et al, 2021 , MedRXiv ) are promising in their utilization of genotyped cohorts in conjunction with questionnaire data and the ability to demonstrate shared genetic bases between reading disorder and other health traits. The goal of extending these lines of research to other speech, language, and reading traits highlights the need for coordinated efforts toward collecting and meta-analyzing large-scale data in cohorts that have been able to link language-related traits to genotypes.…”
Section: Introductionmentioning
confidence: 99%